Key events in the formation of the Kingdom of Serbs, Croats and Slovenes: October 29–December 1, 1918. - Sokcsevits, Dénes (Acta Scientiarum Socialium, 2018)
The birth of the Yugoslavian state in the autumn of 1918 is associated to several symbolic events, such as the treaty of Corfu, the assembly at Újvidék, negotiations in Geneva, and prince regent Charles’ Belgrade manifesto. This paper presents the complex series of events resulting in the formation of the Yugoslavian state on December 1, 1918. Events at each location are discussed, including how these fit in the developments that gave birth to the Yugoslavian state.